Paradigma Formalisasi Hukum Islam di Indonesia - Rahmatunnair Rahmatunnair (AHKAM : Jurnal Ilmu Syariah, 2012)
Abstract: Formalization of an Islamic Law Paradigm in Indonesia. Formalization of Islamic law in Indonesia in principle is an effort of transformation of substantive values of Islamic Law within the system of National law. Indonesia is a constitutional state, so the formalization of Islamic law must refer to the constitution of the state. Therefore, the transformative paradigm of the means of formalization of Islamic law within the constitutional system is an appropriate choice and provides for broader prospects. Thus, the formalization of Islamic law in formal symbolic manner, especially in an effort to establish an Indonesian Islamic State, will only undergo distortions and will not provide benefits for the Islamic community in Indonesia.Keywords: formalization, Islamic law, national constitutionAbstrak: Paradigma Formalisasi Hukum Islam di Indonesia. Formalisasi hukum Islam di Indonesia pada prinsipnya merupakan upaya transformasi nilai-nilai subtanstif hukum Islam dalam sistem hukum Nasional. Indonesia adalah negara hukum, sehingga formalisasi hukum Islam mesti mengacu pada hukum negara. Oleh karena itu, paradigma transformatif bagi upaya formalisasi hukum Islam dalam sistem hukum Nasional adalah pilihan yang tepat dan memberikan prospek yang lebih besar. Dengan demikian, formalisasi hukum Islam secara formal simbolik apalagi dengan upaya mendirikan negara Islam Indonesia, hanya akan mengalami distorsi dan tidak banyak memberikan kebaikan bagi umat Islam Indonesia.Kata Kunci: formalisasi, hukum Islam, hukum NasionalDOI: 10.15408/ajis.v12i1.984